2020
DOI: 10.21037/apm.2020.03.16
|View full text |Cite
|
Sign up to set email alerts
|

A 12-hour comprehensive nutrition care benefits blood glucose level and weight gain and improves outcomes in pregnant women with gestational diabetes mellitus

Abstract: Background: Gestational diabetes mellitus (GDM) is associated with adverse outcomes and neonatal complications. Its prevalence has been rapidly increasing over the last decade; it is estimated that one in six pregnant women are diagnosed with GDM. Thus, an effective management approach is necessary for women with GDM. This study investigated the effect of a 12-h comprehensive nutrition care (12h-HNC) on the metabolism and outcomes of pregnant women with GDM and neonatal birth weight and hypoglycemia. Methods:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…It is worth starting by indicating that the main objective of the interventions reviewed is, in any case, to improve the quality of the diet consumed, and it has been observed that nutritional recommendations should be implemented in conjunction with the appropriate physical exercise in each case. Thus, even if the improvement in the quality of the diet is moderate or minimal, the efficacy in terms of improved maternal and neonatal outcomes is appreciable and positive in all cases [ 17 , 18 , 21 , 24 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth starting by indicating that the main objective of the interventions reviewed is, in any case, to improve the quality of the diet consumed, and it has been observed that nutritional recommendations should be implemented in conjunction with the appropriate physical exercise in each case. Thus, even if the improvement in the quality of the diet is moderate or minimal, the efficacy in terms of improved maternal and neonatal outcomes is appreciable and positive in all cases [ 17 , 18 , 21 , 24 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study found that up to 12 hours of comprehensive nutritional care significantly reduces the incidence of macrosomia in patients with GDM. 21 It has also been shown that dietary control and appropriate exercise can effectively control BG and reduce the incidence of adverse pregnancy outcomes in patients with GDM. 22 The present study aimed to investigate the impact on perinatal outcomes in patients with GDM of the one-day clinic DM management model compared with individualized dietary intervention and exercise guidance.…”
Section: Discussionmentioning
confidence: 99%
“…therapy. [13] However, the argument on the efficacy of medical nutritional therapy and comprehensive nutritional care remains to be resolved. Therefore, we conducted this protocol of systematic review and meta-analysis to evaluate the efficacy between medical nutritional therapy and comprehensive nutritional care for patients with GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive nutritional care is a new method created in recent years to treat GDM. It consists of a nutritious diet, postprandial exercise, health education, and regular follow-up, and is considered a new intervention to replace medical nutrition therapy [13] . However, the argument on the efficacy of medical nutritional therapy and comprehensive nutritional care remains to be resolved.…”
Section: Introductionmentioning
confidence: 99%